231k views
3 votes
The function f is defined by the following rule. f (x)= -3x + 2 Complete the function table.

The function f is defined by the following rule. f (x)= -3x + 2 Complete the function-example-1

1 Answer

4 votes

Okay, here we have this:

Considering the provided function, we are going to calculate the requested values to complete the function table, so we obtain the following:

x=-2:

f(x)=-3x+2

f(-2)=-3(-2)+2

f(-2)=6+2

f(-2)=8

x=-1:

f(x)=-3x+2

f(-1)=-3(-1)+2

f(-1)=3+2

f(-1)=5

x=0:

f(x)=-3x+2

f(0)=-3(0)+2

f(0)=0+2

f(0)=2

x=1:

f(x)=-3x+2

f(1)=-3(1)+2

f(1)=-3+2

f(1)=-1

x=4:

f(x)=-3x+2

f(4)=-3(4)+2

f(4)=-12+2

f(4)=-10

User Till
by
5.1k points